2020
DOI: 10.1039/d0py01098g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of BPA-free polyesters by incorporating a semi-rigid cyclobutanediol monomer

Abstract: The ability of diol monomers, such as 1,4-cyclohexanedimethanol (CHDM) and 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), to replace the potentially hazardous BPA in the production of polyesters and polycarbonates with excellent thermal, optical, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…More toxicological studies are needed to assess the health and safety aspects of TMCD containing TPA copolyesters. [59]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More toxicological studies are needed to assess the health and safety aspects of TMCD containing TPA copolyesters. [59]…”
Section: Discussionmentioning
confidence: 99%
“…When this cyclobutane dimethanol was esterified with TPA, the copolyester had 23.1 kDa M w and 11 kDa M n , and 114 °C T g . [59] On the other hand, 2,4‐diphenylcyclobutane‐1,3‐dicarboxylic acid (Ph 2 CBDA) could be esterified with linear diols like EG and PDO, but the resulting polyesters had T g of only 81 and 64 °C, respectively. [60] Nevertheless, these cyclization reactions based on biomass‐derived intermediates like cinnamic acid and furfual [61] can be beneficial for making greener polyesters.…”
Section: Tmcd Alternatives ‐ Cbdo Substituents For Future Copolyestersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we introduce 2,7-naphtalendiol and 1,1,1-tris(4-hydroxyphenyl)ethane as less toxic alternatives to the widely established toxic and carcinogenic bisphenol-A and resorcin-based polymers, which are increasingly being avoided and replaced by industry. [51][52][53][54][55][56] The condensation and substitution reactions of the prepared aromatic acetoacetates with aliphatic primary amines lead to the formation of blended vinylogous urethane and vinylogous urea compounds, which both undergo thermally induced exchange reactions, thus representing the required dynamic covalent bonds for vitrimers. Model studies are conducted to enlighten the undergoing condensation, substitution and exchange reactions in the emerging vinylogous urethane/urea mixtures, investigating solvent or catalyst effects and comparing activation energies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that CBDAs can be used to produce both thermoplastics and thermosets with excellent properties. ( Amjaour et al., 2019 ; Shahni et al., 2020 ; Wang et al., 2017 , 2018 , 2020 , 2022 )…”
Section: Introductionmentioning
confidence: 99%